Strategi Pengembangan Ternak Sapi Potong Pola Usaha Rakyat di Kawasan Peternakan Kabupaten Ende: Strategy for Development of Beef Cattle Livestock Patterns of People's Business in the Livestock Area of Ende Regency - Yeniria Sofia Ida; Ulrikus Romsen Lole; Tenang Barus; Maria Krova (Jurnal Peternakan Lahan Kering, 2023)
This study aims to analyze the strategy for the development of beef cattle according to the people's business pattern in the livestock area of ​​Ende Regency. The research was conducted in the livestock area of ​​Ende Regency. Data collection techniques used are observation and interviews. The sampling method was carried out in 3 (three) stages, namely stages 1 and 2 carried out purposively and stage 3 carried out by simple random sampling. The analysis used is SWOT analysis. The results of the IFE matrix analysis obtained a total score of 2.605 meaning that internally the development of cattle is strong enough so that the business remains sustainable. The EFE matrix obtained a total score of 3.76, meaning that externally the development of cattle is very strong where the response from the development area has been very good. The results obtained through SWOT diagram analysis are in Quadrant 1, namely supporting aggressive growth policies or very profitable positions. The results of the QSPM analysis, the three main priority strategies that will be implemented are educating farmers regarding maintenance management for the development of cattle business with a total attractiveness score (TAS) of 6.99; procure supporting equipment or technology for processing feed in the form of hay and silage with a TAS acquisition of 4.84 and optimizing the availability of grazing land for cattle development with a TAS acquisition of 4.8. Penelitian ini bertujuan untuk menganalisis strategi pengembangan ternak sapi potong pola usaha rakyat di kawasan peternakan Kabupaten Ende. Penelitian dilakukan di kawasan peternakan Kabupaten Ende. Teknik pengumpulan data yang digunakan adalah observasi dan wawancara. Metode penarikan sampel dilakukan dalam 3 (tiga) tahap yakni tahap 1 dan 2 dilakukan secara purposif dan tahap 3 dilakukan secara simple random sampling . Analisis yang digunakan adalah analisis  SWOT. Hasil analisis matriks IFE memperoleh total skor 2,605 artinya secara internal pengembangan ternak sapi cukup kuat sehingga usaha tetap berkelanjutan. Matriks EFE memperoleh total skor 3,76 artinya secara eksternal pengembangan ternak sapi sangat kuat dimana respon dari wilayah pengembangan sudah sangat baik. Perolehan hasil melalui analisis diagram SWOT berada pada Kuadran 1 yaitu mendukung kebijakan pertumbuhan yang agresif atau posisi yang sangat menguntungkan. Hasil analisis QSPM, tiga prioritas utama strategi yang akan diterapkan yakni mengedukasi petani peternak terkait manajemen pemeliharaan  untuk pengembangan usaha ternak sapi dengan perolehan total attractiveness score (TAS) 6,99; mengadakan alat penunjang atau teknologi  untuk pengolahan pakan berupa hay dan silase dengan perolehan TAS 4,84 dan mengoptimalkan ketersediaan padang penggembalaan untuk pengembangan ternak sapi dengan perolehan TAS 4,8.